Duskside enhancement of equatorial zonal electric field response to convection electric fields during the St. Patrick's Day storm on 17 March 2015. Issue 1 (11th January 2016) - Tulasi Ram, S.; Yokoyama, T.; Otsuka, Y.; Shiokawa, K.; Sripathi, S.; Veenadhari, B.; Heelis, R.; Ajith, K. K.; Gowtam, V. S.; Gurubaran, S.; Supnithi, P.; Le Huy, M.
Abstract: The equatorial zonal electric field responses to prompt penetration of eastward convection electric fields (PPEF) were compared at closely spaced longitudinal intervals at dusk to premidnight sectors during the intense geomagnetic storm of 17 March 2015. At dusk sector (Indian longitudes), a rapid uplift of equatorial F layer to >550 km and development of intense equatorial plasma bubbles (EPBs) were observed. These EPBs were found to extend up to 27.13°N and 25.98°S magnetic dip latitudes indicating their altitude development to ~1670 km at apex. In contrast, at few degrees east in the premidnight sector (Thailand‐Indonesian longitudes), no significant height rise and/or EPB activity has been observed. The eastward electric field perturbations due to PPEF are greatly dominated at dusk sector despite the existence of background westward ionospheric disturbance dynamo (IDD) fields, whereas they were mostly counter balanced by the IDD fields in the premidnight sector. In situ observations from SWARM‐A and SWARM‐C and Communication/Navigation Outage Forecasting System satellites detected a large plasma density depletion near Indian equatorial region due to large electrodynamic uplift of F layer to higher than satellite altitudes. Further, this large uplift is found to confine to a narrow longitudinal sector centered on sunset terminator. This study brings out the significantly enhanced equatorial zonal electric field in response to PPEF that is uniquely confined to dusk sector. The responsible mechanisms are discussed in terms of unique electrodynamic conditions prevailing at dusk sector in the presence of convection electric fields associated with the onset of a substorm under southward interplanetary magnetic field Bz . Key Points: Unusually large equatorial zonal electric field at dusk sector due to eastward PPEF Enhanced electric field limited to a narrow longitudinal sector centered on sunset terminator Unique electrodynamic conditions at sunset terminator are responsible for large zonal electric field